EFEK ATOM SKANDIUM TERHADAP STRUKTURAL DAN SIFAT ELEKTRONIK SENYAWA KALSIUM BOROHIDRIDDIAMONIA SEBAGAI PENGHASIL HIDROGEN : STUDI BERDASARKAN PRINSIP UTAMA AB INITIO DFT - , Muhammad Arsyik Kurniawan S.; , Prof. Dr.rer.nat. Ria Armunanto., M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Study of structure and electronic properties of solid Ca(BH4)2â2NH3 as a hydrogen production material, including doping effect with scandium metal has been performed. The energy, density of states, and band structure of solid Ca(BH4)2â2NH3 have calculated within framework of density functional theory (DFT) by the projector augmented-wave method, and generalized gradient approximation for the exchange-correlation energy functional. Structure analysis and electronic properties of Ca(BH4)2â2NH3 indicated that the source of hydrogen molecule was verified by interaction from hydrogen (HÎ´-) from BHô ô and hydrogen (HÎ´+) from NH3 in dihydrogen bonding site Bâ HâââHâN. The removal energy of hydrogen molecule is 2.30 eV while removal energy of NH3 molecule is 1.52 eV, dissociation of NH3 molecule more dominant than H2. The result of scandium doping give the removal energy of hydrogen molecule is 14 â 22% lower than NH3 removal energy, in this case, removal H2 molecule more dominant than NH3 molecule.